Islamic Education and Multiple Intelligences Implementation in Traditional Game of Sluku-Sluku Bathok at Komunitas Pojok Budaya, Bantul of Yogyakarta - Inayati, Khafidlo Fahri; Millah, Ahmad Sihabul (Jurnal Pendidikan Islam, 2016)
This research is aimed to describe the system within the game of sluku-sluku bathok in the Komunitas Pojok Budaya. This community concerned in reintroducing traditional games among local villagers. Traditional game sluku-sluku bathok at Komunitas Pojok Budaya has many benefits. It is not only to make children happy, but also to stimulate children to develop their multiple intelligences. The benefits can be seen from the moves within the game, togetherness in characteristic of the game, as well as the song they sung. Moreover, the song in sluku-sluku bathok could be used as the implementation of Islamic education.